Chinese Graduate Health Science Students′ Perceptions of Teaching Pedagogies on Their Educational Experience. - Benson, Jeryl D.; Simpson, Richard C.; Hilton, Claudia (Occupational Therapy International, 2025)
This paper explores pedagogical approaches for teaching Chinese graduate health science students by identifying students′ perceptions of teaching and learning strategies that support learning. This study used a survey design to answer the research question: "How do Chinese English as a Foreign Language (EFL) graduate health science students perceive the impact of teaching pedagogies on their educational experience?" Descriptive methods and the Friedman test were used to analyze the data. Data from 34 completed surveys revealed that students perceive responsive instruction and guided feedback (clear, frequent, verbal, and written) as most beneficial to learning. Advance access to notes and materials also supported learning. Student‐led oral discussions and nonverbal communications (via student response systems) were deemed less beneficial. Students valued the opportunity to learn and practice clinical skills in the classroom and the clinic. These findings highlight the need for Western instructors to modify teaching strategies to meet the needs of the EFL learner while maintaining the rigor of the health science curriculum content.